Export activity, R&D investment, and foreign ownership - Sousa, Carlos M P (2021)
Purpose: The paper examines the impact of export activity on productivity and how this effect is moderated by R&D investment and foreign ownership. Design/methodology/approach: A time-lag effect is taken into account when examining the proposed model. Data are collected from the Annual Industrial Survey of the National Bureau of Statistics of China. A dataset containing 117,340 firms across the sample period (2001–2007) are used to test the hypotheses. Findings: The results indicate that while R&D investment plays a significant role in strengthening the positive effect of export activity on a firm's productivity, foreign ownership surprisingly has a negative moderating role. Originality/value: Scholarly interest in the links between export activity and productivity is on the rise. However, the bulk of research has been focused on understanding the effects of export activity on productivity at the country or industry level. Little has been done at the firm level. Another gap in the literature is that the mechanism through which the impact of export activity can be leveraged to enhance the firm's productivity has been largely ignored. To address these issues, the study adopts the learning-by-exporting theory to examine the relationship between export and productivity at the firm-level and how R&D investment and foreign ownership may explain how learning can be leveraged to enhance the firm's productivity. Finally, these relationships are examined in the context of firms from an emerging market, China, which is especially relevant for the learning-by-exporting argument used in this study.